BUKU BESAR DAN KERTAS KERJA PERUSAHAAN DAGANG BAGI SISWA/I SMA BHK - Syanti Dewi; Lalita Cahyarani (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2023)
Trading companies are widely found in our country, especially transactions that affect the assets, liabilities, and capital of the company. All transactions are recorded in the journal, then posted to the general ledger, after which a working paper is created, along with financial statements. The problem faced by the students is to make ledgers and working papers. After more than 2 (two) years, since the pandemic, all schools are still using the online learning system. But for this year, there is an easing for the community to carry out their activities, and so that all schools can conduct face-to-face learning. This material is given, because they have not received the material for the general ledger, trial balance and working papers, so it is important to study it. The number of estimates in the general ledger recorded by the company varies, it all depends on the transactions and financial information of the company, both small, medium and large businesses. The existence of a ledger can produce reliable and timely financial reports. This training was given to high school students of Bunda Hati Kudus Jakarta grade 12 (twelve) science and social studies, with the target of the training being to provide knowledge and insight on how to make ledgers and working papers for trading companies. The results of this activity can increase knowledge about making ledgers and working papers. If they graduate and go straight to work, this can help them by putting their knowledge into practice in the world of work.